Peculiarities of the Physicochemical Properties of Hydrated C60 Fullerene Solutions in a Wide Range of Dilutions - Yablonskaya, O.; Buravleva, E.; Novikov, K.; Voeikov, V. (Frontiers in Physics, 2021)
Hydrated fullerene C60 (HyFn) is a supramolecular object in which the nanosized fullerene molecule is enclosed in a multilayer aqueous shell. HyFn solutions exhibit a wide spectrum of biological activities in particular in high and ultra-high dilutions. To find out if such property of HyFn dilutions may be related to special organization of aqueous systems we compared the character of pH changes in HyFn dilutions and of the corresponding “dilutions” of deionized water when titrating them with either HCl or NaOH. It was shown for the first time that HyFn dilutions had significantly higher buffering capacity against acidification with HCl than control water “dilutions” down to ultra-high dilutions. Besides differences in buffering capacity were revealed between consecutive ultra-high dilutions of HyFn but not in corresponding “dilutions” of control water. These features can arise due to the emergence of heterogenous aqueous regions in HyFn dilutions. Using the method of drying microsphere-containing droplets, whose aqueous bases were either HyFn dilutions or respective water controls it was found that a significant part of HyFn dilutions is characterized by mesoscopic heterogeneity. Thus, HyFn high dilutions differ not only from each other dependently on the dilution level, but also from the respective of water controls.